A bibliometric analysis of studies on gut microbiota in attention-deficit and hyperactivity disorder from 2012 to 2021 - Zhao, Mingyi; Meng, Yang; Cao, Buzi; Tong, Jianbin; Liu, Xiaoying; Yan, Hao; Yang, Hanqi; Han, Houzhi; Liang, Xiaobing; Chen, Hui (Frontiers in Microbiology, 2023)
Background: An increasing number of studies have focused on the role of gut microbiota in the treatment of ADHD, but its related molecular mechanisms are not yet clear, and there is still room for development of studies targeting this area. This study analyzes publications from 2012 to 2021 in a comprehensive and multi-faceted visualization, with the aim of grasping the existing research profile and guiding scholars to make more in-depth studies. Methods: The 1677 articles, 298 review articles on gut microbiota in ADHD were retrieved from the Web of Science Core Collection. We used Citespace, VOSviwer, Microsoft Excel 2019, SCImago Graphica, Bibliometrix and Pajek metrics software for visualization and analysis of the included literature. Results: On August 3, 2022, a total of 1975 English-language articles on gut microbiota in ADHD were retrieved from Web of Science Core Collection (WoSCC) from January 2012 to December 2021, with a steady upward trend in the number of articles published in this field over the decade. The top three countries in terms of the number of articles published are the United States, China and Spain. Meanwhile, CONSEJO SUPERIOR DE INVESTIGACIONES CIENTIFICAS CSIC, UNIV OF CALIFORNIA SYSTEM, and UDICE FRENCH RESEARCH UNIV have made significant contributions in this field. In the analysis of the published journals, PLoS One was not only the first in terms of number of articles published but also the most cited. Wang J was the most prolific author and CAPORASO JG ranked first in terms of co-cited authors. In addition, "Diet rapidly and reproducibly alters the human gut microbiome", published by David LA et al, has the highest citation frequency in this field. The most frequently occurring keyword was "gut microbiota". Conclusion:The results of this paper clarify the current status of research on gut microbiota in ADHD. Most of the studies are still investigating the etiological mechanism of ADHD and searching for its treatment, and we speculate that future studies may focus on "nutrition supplements", "lipid metabolism", and "gut brain axis". We should promote a closer international cooperation among scholars in this field.